Impact of body image on the kinematics of gait initiation - Oku, Kyosuke; Tanaka, Shinsuke; Nishizaki, Yukiko; Fukada, Chie; Kida, Noriyuki (Frontiers in Human Neuroscience, 2025)
In daily life, we walk naturally by considering our physical characteristics and formulating appropriate motor plans. However, the impact of changes in body image on walking movements during motor planning remains poorly understood. Therefore, in this study, we examined changes in walking behavior under different conditions where body image was altered. We included 26 participants (13 men and 13 women, aged 18.27 ± 0.52) who performed walking movements under five conditions: eyes open, eyes covered, eyes covered while imagining their bodies becoming larger, eyes covered without imagining altered body size, and eyes open again. As a result, under the condition where participants imagined their bodies becoming larger, their step length, step completion time, and foot lift height increased. To generate a torque larger than the actual body size, the participants made a motor planning with a larger body image, resulting in an increase in step length. Since these results are attributed to the disparity between actual body size and body image, which affects motor planning, our findings have potential applications in rehabilitation and sports coaching settings.